Cross-sectional study of 1-to-5- year head and neck cancer survivors - Pedro Bastos Cruvinel; Raony Molim de Sousa Pereira; André Luiz de Macedo Fressatti; Bianka Jurca Gonçalves-da Motta; Ana Carolina Fragoso Motta; Harley Francisco de Oliveira; Hilton Marcos Alves Ricz; Leandro Dorigan de Macedo; Camila Tirapelli (Brazilian Journal of Oncology)
Objectives: This study aimed to determine the demographic and clinical profile of 1-to-5year head and neck cancer (HNC) survivors, and they oral features that could affect QoL. Material and Methods: In this cross-sectional study, medical records of 184 were reviewed concerning demographic, clinical and tumour characteristics. 40 of them underwent a quality of life (QoL) questionnaire and assessment of xerostomia (XA), using the oral health impact profile -14 (OHIP-14) and the xerostomia inventory (XI). Salivary flow was determined by measurement of stimulated whole salivary flow rate (SWSFR) and the number of teeth (NT) by determining the number of extracted and/or lost teeth. One-sample t-test, absolute and relative frequencies and Spearman’s correlation test was used for statistical analysis of data. Results: Most HNC patients were male, aged between 50 and 60 years, alcohol and tobacco users, with low educational attainment, several comorbidities, and pharyngeal tumours. The high scores in the OHIP-14 (23.82±14.0) and XI (39.2±7.6) indicated that most patients had their QoL adversely affected and had xerostomia. Mean SWSFR was 0.2mL/ min, and 15% (n=28) of patients were edentulous. The Spearman test showed a significant correlation between QoL and xerostomia, and salivary flow and QoL. Conclusion: This study evaluated characteristics of head and neck cancers (HNC) concerning demographic, clinical and tumour characteristics, quality of life (QoL), xerostomia, salivary flow, and number of teeth (NT) through an observational and cross-sectional study.